ノルウェー カイジョウ ノ ポーラーロー ノ コウクウキ カンソク - 遊馬, 芳雄; アスマ, ヨシオ; 福田, 陽子; フクダ, ヨウコ; 菊地, 勝弘; キクチ, カツヒロ; 塩原, 匡貴; シオバラ, マサキ; 和田, 誠; ワダ, マコト; Moore, G.W.K.; Asuma, Yoshio; et al. (2002)
P(論文) 北極圏航空機観測計画（AAMP 98）期間中の1998年3月9日にノルウェー海上で発生・発達したポーラーローの航空機観測について報告する．客観解析データの解析よりこのポーラーローは上層の正渦位移流と下層の傾圧帯の相互作用によって形成されていた． ポーラーローの中心から伸びる対流雲列を横切るように東西に7高度の水平飛行を行った結果，下層では東西の強い水平温度勾配と強い北風が観測され，温度風の関係を満たしていた．雲内粒子の雲物理観測から，雲粒が下層の大気境界層内で形成され，対流雲内の強い上場流によって急激に上層に運ばれ，氷晶化して降雪粒子となり，さらに周囲の過冷却雲粒を捕捉することで成長し，大きい霞や濃密雲粒付き雪結晶だけが強い上昇流に打ち勝って下層大気に落下している様子が観測された． We will report an airborne measurement of a polar low over the Norwegian Sea on 9 March 1998 during the Arctic Airborne Measurement Program 1998 (AAMP 98). Global objective analysis suggests that the low formed due to an interaction between an upper level potential vorticity anomaly and a low-level baroclinic zone. Seven constant height transects in the zonal direction were made in the convective line clouds associated with the polar low. A strong horizontal temperature gradient in the zonal direction was observed in the lower boundary layer. Gale force northerly winds, in thermal wind balance with this baroclinity, were also observed in the lower atmosphere. departmental bulletin paper